Sustainable Management of Mukim Customary Forests in Aceh Jaya Regency: An Analysis of The Role of Imuem Mukim - Syahroni, Faez; Z, Riswan; Manan, Abdul; Saprijal, Saprijal; Azis, Mohd. (JIAP (Jurnal Ilmu Administrasi Publik), 2024)
In Aceh, there are currently many differences of opinion regarding whether or not mukim should be treated as members of the customary law community in terms of monitoring customary forests. In the context of the country as a whole, mukim are only recognized in the Aceh government structure, while in Indonesia their existence is not recognized. Therefore, a number of parties oppose the authority of mukim in managing Aceh's customary forest land. The purpose of this study was to determine the role and authority of Imuem Mukim and the challenges of sustainable customary forest management in Aceh Jaya Regency. The methodology used was qualitative descriptive, and data collection was carried out through documentation, interviews, and observations. The steps taken in data analysis were data reduction, data presentation, and drawing conclusions. The results of the study showed that Imuem Mukim Panga Pasi and Imuem Mukim Krueng Sabee, who each act as customary leaders and government leaders, have not implemented sustainable management of Aceh Jaya's mukim customary forests. The challenge faced is the lack of community understanding of the importance of the duties and authority of Imuem Mukim in managing mukim customary forests in Aceh, especially Aceh Jaya.